Agricultural commodity markets and the Turn of the month effect - Peter Árendáš; Jana Kotlebová (Agricultural Economics (AGRICECON), 2023)
The Turn of the month (ToM) effect is a calendar anomaly when the majority of returns of an asset are concentrated into several days around the end of the old month and the start of the new one. Until now, the investigation of the ToM effect has mainly been focused on the stock markets. However, this paper investigates the presence of the ToM effect in eight key agricultural commodity markets (cocoa, coffee, corn, cotton, rice, soybean, sugar, wheat), using three different alternatives of the ToM window, during the 2001-2021 time period. The results show a statistically significant ToM effect in the rice, coffee, and sugar markets. Further results show that the ToM pattern changed during the COVID-19 pandemic, and that, in the case of commodities with a statistically significant ToM effect, the ToM effect can be efficiently used to beat the buy & hold investment strategy convincingly.